2010
DOI: 10.2174/1874838401003010024
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Anaphylaxis: A Review of the Incidence, Characteristics and Predictors

Abstract: While it has been recognized for over a quarter century that anaphylactic reactions have the potential to follow a biphasic course, reports on the incidence of biphasic anaphylaxis are conflicting, and the search for reliable predictive factors of such responses has been challenging. Further adding to the complexity of this clinical entity are the widely variable durations of the asymptomatic window, and the similarly variable reports on second phase severity. This review aims to provide the health care profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…38 The association of a biphasic reaction with the severity of the initial reaction has just recently emerged as a potential risk factor. 39 23,34 Although these studies provide some insight about this association, the reported cases are too small to reliably predict this association. Also, the definition of severity used in these studies is inconsistent and not based on objective scoring.…”
Section: Previous Studiesmentioning
confidence: 99%
“…38 The association of a biphasic reaction with the severity of the initial reaction has just recently emerged as a potential risk factor. 39 23,34 Although these studies provide some insight about this association, the reported cases are too small to reliably predict this association. Also, the definition of severity used in these studies is inconsistent and not based on objective scoring.…”
Section: Previous Studiesmentioning
confidence: 99%
“…O tempo entre a exposição ao desencadeante e a reação anafilática variou, e na maioria das vezes foi de no máximo 30 minutos. As evidências disponíveis demonstram que após a resolução do quadro anafilático inicial, 10 a 20% dos pacientes podem ter uma nova onda de manifestações, mesmo na ausência de nova exposição ao desencadeante -reação bifásica 28 , e frequentemente ocorrem na anafilaxia por alimentos 23 . Em nosso estudo apenas um paciente (0,6%) teve anafilaxia bifásica, e a suspeita é que tenha sido desencadeada por droga.…”
Section: Discussionunclassified
“…[72][73][74] It has been noticed that between 10 to 20% of anaphylactic patients may have biphasic reactions, characterized by a second manifestation generally 4 to 6 hours after the first one. 75 However, this second occurrence can happen as late as 78 hours after the first manifestation.…”
Section: -Twomentioning
confidence: 99%